Organopolymerization of multifunctional γ-butyrolactones - Tang, Jing, author; Chen, Eugene Y.-X., advisor; Szamel, Grzegorz, committee member; Miyake, Garret M., committee member; Bailey, Travis S., committee member; Belfiore, Laurence A., committee member (Colorado State University. Libraries, 2018)
The complexity of polymerizations increases drastically as the functionality of monomers increases, which brings about challenges for elucidation of polymerization mechanisms, establishing control of the polymerization, and characterization of the resulting polymer structures. On the other hand, the increased multifunctionality in monomers and polymers offers new opportunities to create polymers with unique structures and interesting properties. The research described in this dissertation demonstrates both challenges and advantages that multifunctionality brings into the polymerization and polymer structures. The first successful polymerization of the naturally occurring, OH-containing, tri-functional monomer Tulipalin B (βHMBL) was achieved by utilizing N-heterocyclic carbene and phosphazene superbase catalysts. Owing to its presence of both the reactive exocyclic double bond and hydroxyl group, the resulting P βHMBL is a branched vinyl–ether lactone copolymer structure with six different types of substructural units. The results reveal multiple types of reaction pathways and their mechanistic crossovers involved in the polymerization, including conjugate Michael and oxa-Michael additions, proton transfer processes, as well as ene-type dehydration reactions, enabled by proton transfer. The reactions of other less complicated multifunctional γ-butyrolactone-based monomers under same conditions was also studied to help uncover the polymerization mechanism, including the polymerization of bifunctional (endocyclic double bond, lactone ring) dihydrofuran-2(3H)-one (FO), 3-methylfuran-2(5H)-one (3-MFO), and 5-methylfuran-2(5H)-one (5-MFO), as well as trifunctional (endocyclic or exocyclic double bond, lactone ring, hydroxyl group) 3-(hydroxymethyl) furan-2(5H) one (3-HMFO). The polymerization of the parent FO leads to a vinyl-addition polymer, while the predominant trimerization and dimerization are observed in the reaction involving the two methyl substituted derivatives, 3-MFO and 5-MFO. The polymerization of trifunctional 3-HMFO gives a poly(vinyl–ether lactone) copolymer structure, via two different types of base activation mechanisms and a combination of Michael and ox-Michael additions and proton transfer processes. This thesis work also investigates how different initiation and termination chain ends of poly(γ butyrolactone) (PγBL) affect the materials properties, including thermal stability, thermal transitions, thermal recyclability, hydrolytic degradation, and dynamic mechanical behavior. Four different chain end-capped polymers with similar molecular weights have been synthesized. The termination chain end showed a large effect on polymer decomposition temperature and hydrolytic degradation. Overall, by chain-end capping, linear PγBL behaves much like cyclic PγBL in those properties sensitive to the chain ends.